Service Imports, Workforce Composition, and Firm Performance: Evidence from Finnish Microdata - Andrea Ariu; Katariina Nilsson-Hakkala; J. Bradford Jensen; Saara Tamminen (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper uses unique Finnish firm-level micro data on service imports, work-force composition, and firm characteristics to examine changes in employment composition and performance of Finnish service importers during a period of a significant increase in services imports (2002-2012). We use world service export supply shocks, which we allocate to firms based on their highly specialized service input structure, as an instrument to identify the impact of service offshoring. We find that firms that increase imports of service inputs reduce employment of low-skill service workers, increase employment of (high-skilled) managers and improve their performance in terms of sales (turnover), assets, service exports, and firm survival. The employment composition and performance responses to service imports differ across firms in the manufacturing sector and those in the service sector.
Keywords: F10; F14; L80; 330; service offshoring; employment; firm performance